1974
DOI: 10.3758/bf03203954
|View full text |Cite
|
Sign up to set email alerts
|

The response criterion, the stimulus configuration, and the relationship between brightness contrast and brightness constancy

Abstract: Four experiments were designed to investigate the nature of the relationship between brightness contrast and brightness constancy while controlling the response criterion, the area of the surround, the stimulus configuration, and the mode of appearance of the modulus target. Ten Os in each of the four experiments estimated the apparent whiteness or brightness of targets with different contrast ratios. All targets were viewed at several illumination levels. Most constancy (whiteness and brightness) functions di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our lightness data from Condition 3 (haploscopic viewing) are compared with Jameson and Hurvich's (1961) lightness data in Figure 2, with our Munsell data in Figure 3, and with our brightness data in Figure 4. DISCUSSION Masuda (1971) and Haimson (1974) also failed to find negative slopes in very close replications of Jameson and Hurvich's (1961) experiment. Arend and Goldstein (in press), using state-of-the-art computer graphics, reported near-perfect lightness constancy, but found that brightness judgments were harder and far from constant, going in the direction reported here (luminance matching).…”
Section: Resultsmentioning
confidence: 72%
“…Our lightness data from Condition 3 (haploscopic viewing) are compared with Jameson and Hurvich's (1961) lightness data in Figure 2, with our Munsell data in Figure 3, and with our brightness data in Figure 4. DISCUSSION Masuda (1971) and Haimson (1974) also failed to find negative slopes in very close replications of Jameson and Hurvich's (1961) experiment. Arend and Goldstein (in press), using state-of-the-art computer graphics, reported near-perfect lightness constancy, but found that brightness judgments were harder and far from constant, going in the direction reported here (luminance matching).…”
Section: Resultsmentioning
confidence: 72%
“…Since the publication of Jameson and Hurvich (1961) , at least four failures to replicate their findings have been reported ( Flock & Noguchi, 1970 ; Haimson, 1974 ; Jacobsen & Gilchrist, 1988 ; Noguchi & Masuda, 1971 ; for a detailed account on the matter, see Gilchrist, 2006 ; for another prospective on the failures, see Taya, 1990 ). Moreover, Arend and Spehar (1993) , in an experiment aimed at studying the effects of illumination on lightness and brightness, found that lightness matching performed by their observers was illuminance independent, even when local luminance contrasts at a target’s edge were not kept constant.…”
Section: Introductionmentioning
confidence: 99%
“…We also cited three other exact replications of the Jameson and Hurvich study (Flock & Noguchi, 1970;Haimson, 1974;Noguchi & Masuda, 1971), all of which failed to find any negative functions. The studies that Heinemann claims agree with Jameson and Hurvich- Helson (1943) and Heinemann (1955)-were merely similar, not replications, and the results match those of Jameson and Hurvich only in the barest way.…”
mentioning
confidence: 93%